Piśmiennictwo rektorów kolegium jezuickiego w Mińsku w epoce saskiej jako przejaw strategii duszpasterskiej i komunikacyjnej Kościoła rzymsko-katolickiego w Wielkim Księstwie Litewskim - Wolański, Filip (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The article presents analysis of writings of the rectors of the Jesuit college in Minsk and elaborates the history and activities of this institution. The achievements of four rectors of Minsk are described: Romuald Wojniłłowicz, author of the collection “Holiday sermons for the whole year”, Józef Stanisław Rudomina, Teodat Ramułt, who wrote plays and short rhetorical works, and Franciszek Ksawery Ogiński, who described the history of St. Michael’s Church in Vilnius.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne